Auditoría de Gestión al Área Administrativa del Grupo de Artillería Ga-7 “Cabo Minacho” Loja. Período: 1 de Enero al 31 de Diciembre del 2015 - García Quito, María Isabel (2017)
The thesis work on management audit was developed in the GA-7 "Cabo Minacho" Artillery Group of the city of Loja, in the period 2015, in order to comply with the General Objective set forth, to evaluate the development of the Activities and propose recommendations that lead to improved institutional management. For the development of this thesis was necessary to propose specific objectives, to analyze the management developed in the unit, which are based on the review of the rules governing the entity, for which the different laws, Regulations, regulations, such as the Armed Forces Personnel Law and Regulation, Internal Regime Regulations for Land Force Units, Military Discipline Regulations, etc. The sub-areas of personnel and operations were evaluated through the application of audit programs. In order to determine the critical areas, an internal control questionnaire was applied, determining a low level of control and a high level of confidence. Found some findings: officials do not legalize documentation, do not take due precautions in training the military personnel, the entity does not have a general functional organization chart which prevents knowledge of staff hierarchy, staff training is not met As planned, there are no constant evaluations to the staff, and narratives were elaborated detailing in each one the findings found in the activities carried out by the entity. Efficiency 5 and effectiveness indicators were also used to determine compliance with the entity's objectives and goals. A final audit report was issued which contains the appropriate conclusions and recommendations that were determined after the management audit was completed, which allowed its managers to make adequate decisions in order to optimize their resources. In conclusion, the summary of the management audit is a synthesis of the investigative work that allowed to determine the degree of fulfillment of the goals, objectives and level of efficiency, effectiveness in the use of available resources. Thus, it allows full control of human and administrative resources to promote progress towards the entity's goals, objectives, mission and vision. In addition, it is recommended that the administrative staff of the entity take into account the recommendations implemented in order to comply with the objectives and goals established in the entity.